A New Smartphone for Every Fifth Person on Earth : Quantifying the New Tech Cycle - Carton, Benjamin (IMF Working Papers; Working Paper ;, 2018)
The enormous global demand for smartphones in recent years has created a new global tech cycle. In 2016 alone, global smartphone sales reached close to 1.5 billion, one for every fifth person on earth. In turn, this has engendered complex and evolving supply chains across Asia. We show that the new tech cycle cannot be captured by standard seasonality, but depends on smartphone product release dates. Decomposing cycle from trend, we also show that the sale of smartphones may have peaked in late 2015. Asia, however, continues to gain in importance as the global tech manufacturer.